Normal Rack Grid Generation Method for Screw Machines with Large Helix Angles. (August 2019) - Yang, Lu; Kovacevic, Ahmed; Read, Matthew
Abstract: Improving the efficiency of the screw machine is highly significant for industry. Numerical simulation is an important tool in developing these machines. The 3D computational fluid dynamic simulation can give a valuable insight into the flow parameters of screw machines. However, it is currently difficult to generate high quality computational grids required for screw rotors with large helix angle. This is mainly due to the excessively high cell skewness of the rotors with large helix angel, which would introduce errors in numerical simulation. This paper presents a novel grid generation algorithm used for the screw rotors with large helix angel. This method is based on the principles developed for the grid generation in transverse cross-section. Such mesh is generated by SCORG TM using normal rack grid generation method which means numerical meshes are generated in a plane normal to the pitch helix line. The mesh lines are then parallel to the helix line and thus an orthogonal mesh will be produced. The main flow and leakage flow directions are orthogonal to the mesh, potentially reducing numerical diffusion. This developed algorithm could also be employed for single screw machines.